Evaluación del uso de semillas de zapallo (Cucúrbita máxima) en la prevención de coccidias en cuyes (Cavia porcellus) durante la fase de engorde - Izurieta Ruiz, Joselyn Stefany (2023)
The evaluation of the use of pumpkin seeds (Cucurbita maxima D) in the prevention of coccidia in guinea pigs (Cavia porcellus L) during the fattening phase, in different concentrations such as high dose 4 mg/kg roasted and unroasted seed and low 2 mg/ kg unroasted roasted seed, to be administered to guinea pigs in the fattening stage. This research shows the efficacy of pumpkin seeds as a natural alternative to chemical drugs to prevent coccidiosis in guinea pigs during the fattening phase. The objective of this study was to determine the most appropriate dose to prevent coccidiosis, and its effect on weight gain in guinea pigs. It was shown that the use of seeds is easily accessible as a natural alternative for deworming and can improve the quality of life of animals. Also, these plants can be easily found in our area. The study found that the use of pumpkin seeds as a preventive of internal parasites (coccidia) in guinea pigs during the fattening phase significantly reduced the incidence of coccidia compared to the control group that did not receive the treatment. In addition, the pumpkin seeds did not present negative side effects compared to the control. The study used a completely randomized design in factorial arrangement (DCA) AxB+1\; with 5 treatments and 3 repetitions, resulting in a total of 15 experimental units with a total of 45 animals under study. Variables such as body weight and the presence of coccidia eggs in the feces of the guinea pigs were evaluated, which were analyzed in the laboratory of the Pontificia Universidad Católica del Ecuador in the School of Agricultural and Environmental Sciences. The 5% Tukey test was used. The results obtained showed to be highly significant for the number of coccidia after treatment. While for the weight gain variable I do not present significance.